Promotion of the Potential and Development of Katembe Beach Tourist Attraction in Madongka Village, Lakudo District, Central Buton Regency Through Instagram Social Media - Yena, Yena; Salakory, Melianus; Tetelepta, Edward Gland (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2022)
The development of tourism potential requires multi-sectoral support in its implementation. With this potential, it can increase local revenue. This research type is descriptive, which describes circumstances, conditions, situations, events, activities, and others. The data collection techniques for this research were observation, documentaries, interviews with research subjects from the tourism office, the Madongka village community, and randomly selected visitors. The opportunity to develop the tourist object offered at Katembe Beach has several attractions, including blushing white sand beaches, beautiful natural scenery, and the uniqueness of the rocks around the beach and other marine ecosystems. The tourism development strategy in managing the area is to provide facilities and infrastructure such as trash cans and food stalls, improve conditions entering the tourist area, and work with the local community.